Improved calibration method for resistive sensors using direct interface circuits - Hidalgo-López, José Antonio; Botín-Córdoba, Jesús Alberto; Sánchez-Durán, José Antonio; Tejero-Calado, Juan Carlos; Oballe-Peinado, Óscar (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Traditional calibration methods for measuring resistance values using a direct interface circuit, comprising a capacitor and some calibration resistors, offer a straightforward, economical option. However, such methods show greater inaccuracies as resistance values decrease. This article presents a modification of the method that ensures more accurate measurements and extends the range of resistance values that can be measured. Unlike the linear equation used in the traditional method, the proposed method obtains power functions related to resistance value and measured discharge time. Since these circuits need calibration resistors, criteria are established to find their values. To reduce arithmetical complexity two approximations are tested to calculate the exact value of the resistance. With this approach, the relative errors for low resistances are reduced and the measuring range is extended. Three measurement set-ups were carried out with a microcontroller and an FPGA to validate the results, showing the validity of the method independently of the device. Using the FPGA configured so that the maximum current that can be sink per output pin is 24mA, the error in the estimation of a resistance of 9.9 Ω is 10 times less than that obtained using the classic two points calibration method.
(c) 2019 Crown Copyright. Personal use is permitted. For any other purposes, permission must be obtained from the IEEE by emailing pubs-permissions@ieee.org. " Versión Aceptada descargada del "IEEE Author Gateway". IEEE autoriza a publicar esta versión en repositorios institucionales".
Keywords: Circuitos electrónicos; Sensores; Direct interface circuits (DICs); Error reduction; Interface sensor; Resistive sensor; Time-based measurement; Error analysis